A review on technology transfer in context of multinational corporations - Syed Ali Fazal; Sazali Abdul Wahab (2014)
Since the world has evolved as a Global Village, new technological innovation has become crucially important for sustaining market competition and gaining competitive edge irrespective of size and sector of any organization. Multinational Corporations mostly enjoying technologically advanced positions play vital role in disbursing technological knowledge throughout firms globally. This paper would enrich existing literature by observing different aspects related to technology transfer and outlining the relationship between multinational corporations and technology transfer that is, the role played by MNCs in relocating technological knowledge worldwide. This review would stimulate plots for prospective researchers to recognize and explain technology transfers by multinational corporations specially focusing on the parties and the process involved in intra inter-firm and intra-firm transfer of technology at the same time.